Traumatic reticuloperitonitis in a flock of sheep - Baydar, E.; Kulualp, K.; Eroksuz, Y.; Karapinar, T.; Eroksuz, H. (Taylor & Francis Ltd, 2016)
(The objective of this study was to describe the clinical, ultrasonographical, and pathological findings of traumatic reticuloperitonitis (TRP) with its complications in a flock of sheep. Thirteen sheep in a flock died within one month's duration before two sheep were admitted to the Firat University Veterinary Medical Teaching Hospital. Three additional dead sheep were submitted for necropsy. A tentative diagnosis of TRP on two of the sheep was made based on clinical and ultrasonographic findings. A needle perforating the reticulum was removed from each sheep by surgery. The two sheep improved after the surgery. The necropsy revealed fibrous adhesions and a fistular connection between the dorso-ventral face of the reticulum to diaphragma and pericardium with 3 cm syringe needles in the other three sheep. There were congophylic amyloid deposits in the glomerular tufts, Bowman capsule and vascular walls of the liver, kidneys and spleen. Additionally, there was centrilobular necrosis indicating heart failure.Taken together; TRP is rarely seen in sheep; however, TRP and its complications may cause economic losses in sheep flocks. Ultrasonographic examination of the reticular area in sheep may be used as an ancillary diagnostic technique.
Keywords: amyloidosis; sheep; traumatic reticuloperitonitis; ultrasonography